3D Stress intensity factor and T-stresses (T11 and T33) formulations for a Compact Tension specimen (Fracture and Structural Integrity, 2016)
The paper describes test specimen thickness effect on stress intensity factor (KI), and T-stresses stresses (T11 and T33) for a Compact Tension specimen. Formulations to estimate 3D KI, T11 and T33 stresses are proposed based on extensive 3D Finite element analyses. These formulations help to estimate magnitudes of 3D KI and T11 and T33 which are helpful to quantify in-plane and out-of- plane constraint effect of the crack tip. The proposed formulations are validated with the similar results available in literature and found to be within acceptable error.
Keywords: Constraint effects; 3D Finite element analysis; Stress intensity factor; T-stress; CT Specimen